Hearing Loss in Diabetic Patients: A Prospective Comparative Study - Rijal, Shivaji; Gautam, Dipendra; Pantha, Tridip; Karki, Buddha Bahadur; Kayastha, Sudin; Kadariya, Jagriti (Nepal Journal of Health Sciences, 2025)
Introduction: Diabetes mellitus is a chronic systemic disorder characterized by hyperglycemia, various systemic metabolic derangements and complications. Recent research has increasingly reported hearing impairment as one of the complications of diabetes mellitus. The relationship between diabetes and hearing loss has been a subject of investigation for many years.Objective: To evaluate the hearing status of diabetic patients compared with non-diabetic controls and to assess the association of hearing loss with age and duration of diabetes.Methods: A prospective comparative study was conducted in the Department of Ear Nose Throat, Head and Neck Surgery, Bir Hospital, NAMS, Kathmandu, from May 2021 to May 2022. Pure tone audiometry was performed on 89 type 2 diabetes mellitus patients and 89 age matched non-diabetic controls aged 35–60 years. Hearing thresholds were compared between groups, and associations with age and duration of diabetes were analyzed.Results: The mean age of diabetic patients was 48.8 years compared to 46.6 years in controls. Among diabetics, 35.95% demonstrated some degree of sensorineural hearing loss with a mean hearing threshold of 30.23 dB, whereas only 12.3% of healthy controls had hearing loss, with a mean threshold of 24.66 dB. The difference was statistically significant (p